Analyzing Imam Al-Darimi's Criticisms of His Mentor Ibn Maeen in Hadith Scholarship - Zaid Antary; Islam Tazaza (Presscience, 2024)
This study critically examines the discrepancies between Imam Al-Darimi and his teacher, Imam Ibn Maeen, within the framework of Hadith criticism (ʿilm al-rijāl). Addressing the misconception that classical students passively transmitted their teachers' views, the research analyzes instances where Al-Darimi contested Ibn Maeen’s evaluations of narrators in his work Al-Tarikh. Employing an inductive-analytical methodology, the authors cataloged 31 critical discrepancies out of 975 examined narrations. These instances reveal Al-Darimi’s independent scholarly rigor, particularly in modifying Ibn Maeen’s critiques (jarḥ) or validations (taʿdīl) of narrators. Key findings underscore Al-Darimi’s mastery of Hadith criticism, his nuanced balance of respect and intellectual autonomy toward his teacher, and the broader implications for understanding classical Islamic scholarship. The study concludes that critical engagement, even with revered authorities, was integral to preserving the integrity of Hadith transmission. By contextualizing these discrepancies through principles of narrator evaluation, the research contributes to debates on scholarly authority, methodological diversity, and ethical critique in early Islamic jurisprudence.